Material didáctico y desarrollo del lenguaje oral en los niños de subnivel preparatoria de 5 a 6 años - Cun Chicaíza, Evelyn Elizabeth; Castillo Chocho, Karina Elizabeth (Machala, 2022)
The objective of this research work was to determine the relationship that exists between the didactic material and the development of oral language in children of the preparatory sublevel from 5 to 6 years of age of the "Héroes de Jambelí" basic education school in the city of Machala. The applied research methodology was quantitative in nature, since it focused on the collection of theoretical bases and data tabulation. To achieve this, a structured interview was applied to the teachers and a checklist to evaluate the infants. The results obtained show that high school students need contact with materials that induce them to participate and express themselves during an activity. For this reason, a didactic guide was proposed, addressed to the teachers of the institution, to improve their teaching and offer students greater possibilities of development in the area of oral language, through dynamic classes that involve the manipulation of pedagogical material. Implementing didactic materials represents an important benefit for the educational process, among its characteristics, they must be dynamic, attractive to the eye, easy to use, capable of provoking interaction and individual or group learning, since they promise to help infants. to build knowledge, and achieve the abilities and skills outlined in the high school curriculum. One of the conclusions of this study indicates that the training of teachers and their search to find new and dynamic materials that arouse the curiosity of their students must be constant. In addition, the evaluation of the same before being incorporated into the classes allows to know their functionality, handling, and if they are adapted to the interests and age of the children.
El presente trabajo investigativo tuvo por objetivo determinar la relación que existe entre el material didáctico y el desarrollo del lenguaje oral en niños de subnivel preparatoria de 5 a 6 años de la escuela de educación básica “Héroes de Jambelí” de la ciudad de Machala. La metodología de investigación aplicada fue de corte cuantitativo ya que se centró en la recopilación de bases teóricas y tabulación de datos. Para lograrlo se aplicó una entrevista estructurada a las docentes y una lista de cotejo para evaluar a los infantes. Los resultados obtenidos exponen que los estudiantes de subnivel preparatoria necesitan del contacto con materiales que les induzcan a participar y expresarse durante una actividad. Por ello se propuso ante lo expuesto una guía didáctica, dirigida a las docentes de la institución, para mejorar su enseñanza y brindar a los educandos mayores posibilidades de desarrollo en el área del lenguaje oral, mediante clases dinámicas que involucren la manipulación del material pedagógico. Implementar materiales didácticos representa un beneficio importante para el proceso educativo, entre sus características, deben ser dinámicos, atractivos a la vista, de fácil uso, capaces de provocar la interacción y el aprendizaje individual o en grupo, ya que así prometen ayudar a los infantes a construir conocimientos, y alcanzar las habilidades y destrezas planteadas en el currículo de preparatoria. Una de las conclusiones de este estudio indica que la capacitación de las maestras y su búsqueda por encontrar materiales nuevos y dinámicos que despierten la curiosidad de sus estudiantes deben ser constante. Además, la evaluación de los mismos antes de ser incorporados a las clases permite conocer su funcionalidad, manejo, y si se adecuan a los intereses y edad de los niños.
Keywords: MATERIAL; NIÑO; DOCENTE; LENGUAJE ORAL; GUIA DIDACTICA